An adaptive ensemble localization approach for sensor nodes in WSN-IoT - Ravi Sharma; Shiva Prakash (EAI Endorsed Transactions on Energy Web, 2020)
Localization is an essential module for most protocols and applications in Wireless Sensor Networks - Internet of Things(WSN-IoT). Among the well-known approaches available for WSN-IoT localization, the algorithm requires at least one,two, or three beacon nodes-based localization approaches. Many other localization protocols use a small set of beacon nodesfor the localization of sensor nodes. However, still, the authors are not able to provide an accurate and reliable approach inthe field of WSN-IoT. Thus, this work provides an adaptive ensemble localization approach in WSN-IoT. The proposedapproach adaptively uses the concept of available single, two, and three beacons nodes-based localization approachesaccording to the number of available beacon nodes. By comparing available single, two, or three beacons nodes-basedlocalization approaches the simulation results of the proposed work outperformed in terms of fast convergence rate, lesserroneous and higher accuracy with reducing the line of sight problem.